Pengaruh Gaya Kepemimpinan, Lingkungan Kerja, dan Motivasi Kerja Terhadap Kinerja Pegawai Pada Dinas Peternakan dan Kesehatan Hewan Kabupaten Tulang Bawang Barat - Rendy Julian Saputra; Ni Putu Widhia Rahayu (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
Improving employee performance is a crucial factor in supporting the effectiveness and quality of public services, particularly at the Department of Animal Husbandry and Animal Health of Tulang Bawang Barat Regency. Optimal employee performance contributes to the achievement of organizational goals and enhances public trust in government institutions. The problem addressed in this study is the need to optimize leadership style, work environment, and work motivation management in order to improve employee performance. This study aims to analyze the influence of leadership style, work environment, and work motivation, both partially and simultaneously, on employee performance. This research employed a quantitative method with descriptive and verificative approaches. The population consisted of 40 employees, and a saturated sampling technique was applied, meaning all employees were included as respondents. Data were collected through questionnaires using a Likert scale, and the analysis was conducted using multiple linear regression with the assistance of statistical software. The results indicate that partially, leadership style, work environment, and work motivation have an effect on employee performance, and simultaneously, these three variables significantly influence employee performance. Among the variables, work motivation has the most dominant effect on employee performance. Therefore, it is recommended that institutional leaders enhance leadership quality, create a conducive work environment, and strengthen employee motivation to achieve sustainable performance improvement.